The Development of Student Worksheet Based on Contextual Approach about Coordination System 11th Grade Senior High School - Nisa Ayunda Rahmi Mutia; Ganda Hijrah Selaras; Rahmadhani Fitri; Ristiono Ristiono (Universitas Negeri Padang, 2020)
This research in general is aimed to develop student worksheet base on contextual approach on the coordination system for senior high school in grade 11 using metode of 4-D development. The subjects of this research is one of lecturer majoring in biology at Padang State University, two teachers of SMAN 3 Padang, and 30 students in grade 12 of SMAN 3 Padang as potential users of the product. Data that used in this research is primary data. Instrument of data collection in this research is a questionnaire of validity and practicalicity filled out by expert and students. The result for validity is 91,2% that criteria is very valid. Result for practicalicity from teacher is 90,5% that criteria is very practical and from stucent is 81,3% that criteria is practical.st